Original Sin and Everyday Protestants : The Theology of Reinhold Niebuhr, Billy Graham, and Paul Tillich in an Age of Anxiety - Finstuen, Andrew S. (Book collections on Project MUSE., 2009)
Finstuen deals with the reception of original sin by the people in the pews. In the years following World War II, American Protestantism experienced tremendous growth, but conventional wisdom holds that midcentury Protestants practised an optimistic, progressive, complacent, and materialist faith. Finstuen argues against this view, showing that theological issues in general - and the ancient Christian doctrine of original sin in particular - became important to both the culture at large and to a generation of American Protestants during a postwar 'age of anxiety' as the Cold War took root.